(untitled) (Journal Intellectual Sufism Research (JISR), 2024)
Abstract This article is an area survey article. The purpose of this study was to study the characteristics of Dajjal in the Dikia songs of Muslims Koh Yao Noi. The first part of the article presents the details of the Dajjal in the Islamic text. The second part presents about Dikia songs of Muslims Koh Yao Noi. The last part presents the characteristics of the Dajjal in the Dikia song. The article finds that Da Jai is a word or name that is used in place of Dajjal in the Dikia song. The characteristics of the Da Jai in the Dikia song are different from those of the Dajjal in Islamic text, because the Dajjal in the Islamic texts states that he is only human and does not have a different shape from humans but has the power to deceive and persuade humans. However, the purpose of the Dikia song is to warn of the crisis that will come near the Day of Resurrection with many divine trials, hunger, drought, and difficult situations. The Dajjal will come out to convince the Muslims to lose their faith in God. Thereby, Dikia song attempts to portray the Dajjal as a Yak or giant who will destroy humanity with power and deception.